Answer:
a)[tex]X= kA_o\dfrac{1}{k^2+\omega^2}\left ( kcos\omega t+\omega sin\omega t \right )+Ce^{-kt}[/tex]
b)Does not affect the long term.
Explanation:
Given that
[tex]\dfrac{dx}{dt}=-k(x-A)[/tex]
A = A0 cos(ωt)
[tex]\dfrac{dx}{dt}=-k(x-A_o cos(\omega t))[/tex]
[tex]\dfrac{dx}{dt}+kx=kA_o cos(\omega t)[/tex]
This is linear equation so integration factor ,I
[tex]I=e^{\int kdt}[/tex]
[tex]I=e^{kt}[/tex]
Now by using linear equation property
[tex]e^{kt} X=\int e^{kt} kA_o cos(\omega t) dt +C[/tex]
[tex]e^{kt} X= kA_o \dfrac{e^{kt}}{k^2+\omega^2}\left ( kcos\omega t+\omega sin\omega t \right )+C[/tex]
[tex]X= kA_o\dfrac{1}{k^2+\omega^2}\left ( kcos\omega t+\omega sin\omega t \right )+Ce^{-kt}[/tex]
b)
at t= 0
[tex]X(0)=\dfrac{k^2A_o}{\omega^2+k^2}+C[/tex]
[tex]X= kA_o\dfrac{1}{k^2+\omega^2}\left ( kcos\omega t+\omega sin\omega t \right )+e^{-kt}\times \left ( X(0)-\dfrac{k^2A_o}{\omega^2+k^2} \right )[/tex]
So the initial condition does not affect the long term.